2023
DOI: 10.1101/2023.03.20.533463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contingency, Repeatability and Predictability in the Evolution of a Prokaryotic Pangenome

Abstract: Pangenomes exhibit remarkable variability in many prokaryotic species. This variation is maintained through the processes of horizontal gene transfer and gene loss. Repeated acquisitions of near-identical homologs can easily be observed across pangenomes, leading to the question of whether these parallel events potentiate similar evolutionary trajectories, or whether the remarkably different genetic background of the recipients mean that post-acquisition evolutionary trajectories end up being quite different. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…According to previous studies 1012 , certain bacterial genes had significant co-occurrence/avoidance patterns. Thus, the correlation between accessory gene status and cgST in Supplementary Fig 6 might actually result from the gene co-occurrence phenomenon.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…According to previous studies 1012 , certain bacterial genes had significant co-occurrence/avoidance patterns. Thus, the correlation between accessory gene status and cgST in Supplementary Fig 6 might actually result from the gene co-occurrence phenomenon.…”
Section: Resultsmentioning
confidence: 84%
“…Regarding to relationship among genes, previous studies 1012 had found that large amount of bacterial genes could display co-occurrence or avoidance patterns with one another, and some studies on Listeria monocytogenes had presented a strong correlation between core genome based sublineage and accessory gene presence 1316 . In L. monocytogenes , internalin A ( InlA ) is an example of gene-gene sequence variants correlation.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one must also consider the emerging role of intra-genomic selective pressures in determining the composition of prokaryotic genomes and that these niche-adapted genes may have positive or negative effects on other genes within the pangenome [102,103]. The absence of LTTR encoding genes from a 608 kb region of the P. aeruginosa genome will be fascinating to investigate for such patterns of exclusion and inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the importance of comprehensive training data. While evolution can be both contingent and deterministic [88]; a ML-based investigation [89] aligns with the deterministic theory, and some methods [42,90] have achieved moderate AMR phenotyping accuracy using phylogenetic information, indicating potential efficacy of exclusively utilizing ancestral lineages for training ML models in the absence of comprehensive data. Lastly, the third hypothesis suggests that the combined effects of AMR variants and lineage backgrounds could impact the efficacy of ML-derived predictors, as indicated by the genome misclassification frequency.…”
Section: Discussionmentioning
confidence: 99%